The influence of social changes on the development of Chinese and Western cultural industries - Yangguang, Qiu; Selchenok, Elena K. (Human in the Socio-Cultural Dimension, 2021)
The article analyses the enlightenment of the mature system of the development of the cultural industry in the West in the social changes to the development of the Chinese cultural industry. Chinese cultural industry development must first seize the two social structural opportunities of social industrialisation and social informatisation, explore the path of digital transformation, innovate national characteristics, transform traditional cultural resources into digital information carriers, and extend and promote cross-field industry chain integration and establish and improve the basic economic system, realise the value-added of each link of the cultural industry content value chain, give full play to the role of the industrial system in ensuring the effective operation of the market, promote the development of upgrading, and promote the development of Chinese cultural industry through the innovation of the cultural industry system. The author believes that the cultural industry system should shift from the government demand side to the market development demand side. Only by improving the process of the cultural industry system and promoting the integration of cross-field industrial chains can the development of Chinese cultural industry be promoted.